Gaidam regime’s social welfare performance in achieving democratic consolidation in Yobe State, Nigeria - Abbas, Ali Ibrahim (2017)
The study provides analysis of the regime’s social welfare performance of Governor Gaidam in achieving democratic consolidation in Yobe state regarded as one of the most underdeveloped states in Nigeria. Since the emergence of democracy in the state, the healthcare situations such as infant mortality, children under-five mortality and maternal mortality rates were all higher than the national average. In the education sector, the situation remained worrisome as student’s enrollment; completion rate at both primary and secondary schools in the state was low. Similarly, infrastructural development such as road access linking towns and villages were either absent or in deplorable conditions. Consequently, due to such extreme situations, the state was generally considered impoverished and underdeveloped which continue to pose negative consequences on its democratic consolidation. When Governor Gaidam came into power in 2009, the regime declared to address these social welfare challenges through the democratic process. The objectives of this study, therefore, explored the regime’s development objectives in social welfare aspects and assessed the impact the regime’s welfare performance on democratic consolidation. Through qualitative research design, the study specifically involved key democratic stakeholders including members of the ruling party, opposition parties as well as civil society groups in Yobe state. Thus, data collection technique involves semi-structured open-ended interviews purposively with key informants and document analysis through the qualitative lenses. Observational data were also converted to field notes for data analysis. The raw data were analysed using transcription and sorting to develop trends, patterns, and themes emerging from expressed view of informants. In essence, this study utilised both primary and secondary sources of data that produced a balanced result. The finding suggests a double-sided phenomenon: on one hand the euphoria of change and improvement; on the other hand; critical view of the regime’s social welfare performance deficits in the provision of quality and accessible health care, qualitative and functional education as well as the regime’s efforts in road construction and reconstruction across Yobe state. The study further identified reasons for the regime’s success and failures in delivering healthcare, education and road infrastructure in achieving democratic consolidation. As the finding reveals, in spite of the major challenges the regime faced, a nascent democratic government like in Yobe state must perform optimally to respond to citizen’s social welfare demands in order to achieve democratic consolidation. Democracy in this sense is thus propagated not only as a goal in itself but is considered as an instrument that brings about social welfare achievements to the fore in democratic consolidation process through better institutions and structures of democratic governance.